An introduction to Israel's wisdom traditions - McLaughlin, John L. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2018)
It can be a challenge to understand the Hebrew Bible's wisdom literature and how it relates to biblical history and theology, but John L. McLaughlin makes this complicated genre straightforward and accessible. This introductory-level textbook begins by explaining the meaning of wisdom to the Israelites and surrounding cultures before moving into the conventions of the genre and its poetic forms. The heart of the book examines Proverbs, Job, Qoheleth (Ecclesiastes), and the deuterocanonical Ben Sira and Wisdom of Solomon. McLaughlin also explores the influence of wisdom throughout the Old Testament and in the New Testament. Designed especially for beginning students--and based on twenty-five years of teaching Israel's wisdom literature to university students--McLaughlin's Introduction to Israel's Wisdom Traditions provides an informed, panoramic view of wisdom literature's place in the biblical canon. -- ! From publisher's description.
Introduction: The nature of wisdom -- The international context for Israel's wisdom -- The expression of wisdom -- Proverbs -- Job -- Qoheleth -- Ben Sira -- The wisdom of Solomon -- Wisdom influence in the first Testament -- Wisdom theology -- The continuation of wisdom.
Includes bibliographical references and indexes.
Print version record.
Keywords: Bible -- Criticism, interpretation, etc; Wisdom literature -- Criticism, interpretation, etc; Bible; Wisdom literature; RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Studies / Wisdom Literature; Criticism, interpretation, etc; Electronic books